DEATHS BY COVID-19 IN THE STATE OF BAHIA: FROM CAPTURE TO PUBLICATION - Lima, Joyce Naiana de Paiva (2021)
Initially identified in Wuhan, China, Covid-19 caused by the respiratory syndrome coronavirus (SARS-CoV-2) has triggered a global alert. Faced with this emergency scenario, Brazil, like other countries, has been experiencing major changes in health actions and services. In the state of Bahia, the rapid spread of the disease increased significantly the notification of cases and deaths, promoting a restructuring in the work process of state epidemiological surveillance to act in a timely manner in capturing, investigating and classifying cases, publishing and recommending sanitary measures. This paper aims at describing the work process in the epidemiological surveillance of deaths by Covid-19 in the state of Bahia. This is an experience report of Covid-19 death analysis work process, from March to December 2020. The methodological trajectory was structured in document analysis, investigation reports, notification tools from the Ministry of Health and others official systems, and the SUS FormSUS Electronic Form, produced by the Epidemiological Surveillance Directorate (Divep) to identify deaths by Covid-19 by hospitals in Bahia in a timely manner, facilitating the process of capturing, investigating, analyzing and publishing information of mortality. It was observed that the structuring of an organized process and application to the workflow enabled the qualification and reliability of death information by Covid-19, ensuring incremental changes in the scope of surveillance and security in the published information, essential for planning prevention and control actions.